AUGMENTED REALITY AND SITUATED GRAMMAR LEARNING IN PRIMARY EFL CLASSROOMS: A QUASI-EXPERIMENTAL MIXED-METHODS STUDY - Nur Fatimah; Khoirul Anwar (University of Kuningan, 2026)
Augmented reality (AR) offers contextual and visual support for primary EFL learners; however, empirical evidence on AR-supported grammar learning in primary classrooms remains limited. This explanatory sequential mixed-methods study examined how AR-supported situated grammar instruction supported second-semester fourth-grade students’ learning of the present continuous tense. Sixty students from SD Negeri Topogaro, Morowali, Central Sulawesi, participated in a quasi-experimental pre-test-post-test control group design. Class 4A served as the experimental group (n = 30), and Class 4B served as the control group (n = 30). The experimental group learned through Assemblr Edu AR markers, collaborative sentence construction, and situated task presentation, while the control group received conventional grammar instruction. The experimental group obtained higher post-test scores (M = 87.67, SD = 8.73) than the control group (M = 75.73, SD = 8.48). ANCOVA confirmed a significant group effect after controlling for pre-test scores, F(1, 57) = 54.70, p < .001, partial eta squared = .490, with an adjusted mean difference of 11.55 points. The questionnaire, administered only to the experimental group after the intervention, showed very positive post-intervention perceptions (M = 4.47/5.00). Qualitative findings indicated that AR supported grammar learning through authentic context, embodied learning, collaboration, and visual anchoring. The findings suggest that AR can function as a complementary scaffold for contextualized grammar learning.